How Does Extended Maceration Affect Tannin and Color of Red Wines from Cold-Hardy Grape Cultivars? - Aude A. Watrelot; Nicolas Delchier (Foods)
Red wines produced with interspecific grape cultivars tend to have low tannin concentration and are therefore unbalanced. Extended maceration (EM) is a common winemaking technique which can promote the extraction of tannins from grape skins and seeds. The goal of this study was to evaluate the effect of EM on the tannin concentration, color intensity and other chemical properties of red wines made from cold-hardy grape cultivars. The wines were made from two cold-hardy interspecific grape cultivars (Marquette, and Petite Pearl) for either 7 days (control) or 21 days (EM) before pressing. Chemical analysis of the wines was conducted to determine their tannin concentration and color parameters at different stages of the process and after 14 months of aging. EM resulted in an improvement in the iron-reactive phenolic content of Marquette red wines (from 582 to 969 mg/L at bottling in control and EM wines, respectively), but no significant improvement in tannin content. The hue of Petite Pearl wines increased following EM only at pressing, and color intensity of those wines decreased at pressing and bottling by 43% and 52%, respectively. This study was the first one conducted on non-Vitis vinifera grapes which showed a lack of impact of EM on the phenolics and tannin concentration in the red wines made in 2022.